The Journey of Unicorn Uber from San Francisco to International Disruption. Issue 1 (March 2018) - Barot, Haresh; Chhaniwal, Poonam V.
Uber, one of the most valuable and talked about private start-ups of today's time, took the transportation industry by storm through its technology enabled transportation solutions. This case study explores the journey of Uber from its inception to being one of the most valuable new organizations. It also tries to explore the various issues which the company countered in its journey of expansion and growth.